2022
DOI: 10.21037/jgo-21-470
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsies for colorectal cancer: a narrative review of ongoing clinical trials and the current use of this technology at a comprehensive cancer center

Abstract: Objective: In this review, we summarize ongoing clinical trials involving liquid biopsies (LB) for colorectal cancer (CRC), outlining the current landscape and the future implementation of this technology. We also describe the current use of LB in CRC treatment at our institution, the Mayo Clinic Enterprise.Background: The use of LB in CRC treatment merits close attention. Their role is being evaluated in the screening, non-intervention, intervention, and surveillance settings through many active trials. This,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Now multimodal liquid biopsy-based test (LUNAR-2 or Shield Test) is on trial and showing promising results for early detection of CRC. This test includes ctDNA assessment of somatic mutations, tumor-derived methylation, and cfDNA fragmentations ( Broccard et al, 2022 ). The ctDNAs are small fraction of cfDNA that mainly derived from primary tumors, metastatic tumors, and CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Now multimodal liquid biopsy-based test (LUNAR-2 or Shield Test) is on trial and showing promising results for early detection of CRC. This test includes ctDNA assessment of somatic mutations, tumor-derived methylation, and cfDNA fragmentations ( Broccard et al, 2022 ). The ctDNAs are small fraction of cfDNA that mainly derived from primary tumors, metastatic tumors, and CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…A large sample analysis has demonstrated that ctDNA may be a feasible biomarker for various solid tumor types. 38 Moreover, ctDNA could provide longitudinal and dynamic surveillance of the tumor-specific genetic characteristics without having to repeatedly perform invasive tumor biopsies that cost more time and money. 39 In our study, serial ctDNA dynamic changes in predicting tumor responses and survival outcomes revealed that patients with a >50% decline in maxVAF between the first clinical evaluation and baseline had longer survival outcomes and higher response rates than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy is a novel category aiming to detect circulating cancer, including circulating tumor cells, circulating tumor DNA, and cell-free DNA ( 6 ). Currently, there are 35 liquid biopsy CRC trials ongoing to help establish their clinical utility ( 7 ); however, a potential problem is the need for sufficient tumor volume, which challenges its suitability for screening purposes. Developing a blood-based screening test targeting precancerous events would be an appealing approach.…”
Section: Introductionmentioning
confidence: 99%